2013
DOI: 10.1586/17476348.2014.860357
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-related disorders in chronic obstructive pulmonary disease

Abstract: Sleep may have several negative consequences in patients with chronic obstructive pulmonary disease (COPD). Sleep is typically fragmented with diminished slow wave and rapid-eye-movement sleep, which likely represents an important contributing factor to daytime symptoms such as fatigue and lethargy. Furthermore, normal physiological adaptations during sleep, which result in mild hypoventilation in normal subjects, are more pronounced in COPD, which can result in clinically important nocturnal oxygen desaturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 92 publications
0
10
0
1
Order By: Relevance
“…The coexistence of obstructive sleep apnea syndrome and COPD is common, and it is called overlap syndrome [30]. In patients with overlap syndrome, nocturnal oxygen desaturation is severe and the prevalence of PH is very high.…”
Section: Sleep Apnea and Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…The coexistence of obstructive sleep apnea syndrome and COPD is common, and it is called overlap syndrome [30]. In patients with overlap syndrome, nocturnal oxygen desaturation is severe and the prevalence of PH is very high.…”
Section: Sleep Apnea and Copdmentioning
confidence: 99%
“…In patients with overlap syndrome, nocturnal oxygen desaturation is severe and the prevalence of PH is very high. In acute exacerbation in patients with overlap syndrome, noninvasive pressure support is known to be beneficial [30]. However, the evidence is limited to whether the pressure support therapy is effective in the chronic setting of COPD patients without obstructive sleep apnea [30].…”
Section: Sleep Apnea and Copdmentioning
confidence: 99%
“…COPD patients who develop hypercapnia have a particularly poor prognosis 24. The pathophysiological processes underlying chronic hypercapnic respiratory insufficiency in COPD are not completely understood, but proposed mechanisms include increasing respiratory muscle insufficiency,5,6 increased dead volume ventilation7 and, in particular, changes in respiratory regulation during sleep 8. Compared with individuals with healthy lungs, COPD patients are more susceptible to hypoventilation during sleep; the extent of hypoventilation during sleep depends on the extent of pulmonary function impairment9 and occurs particularly during rapid eye movement (REM) sleep.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it has been reported that sleep‐related symptoms in COPD may be related with significant changes in respiratory center, airway resistance and muscle contractility during sleep . These changes result in decreased sleep efficiency, prolonged time to fall asleep, reduction in total sleep time and increase in waking frequency, all leading to daytime sleepiness and worsening sleep quality . Poor sleep quality may cause exacerbations and mortality but it is not related with disease severity .…”
Section: Introductionmentioning
confidence: 99%